2002
DOI: 10.1017/s0022029902005538
|View full text |Cite
|
Sign up to set email alerts
|

Variations of lactoperoxidase activity and thiocyanate content in cows' and goats' milk throughout lactation

Abstract: S. Lactoperoxidase activity and thiocyanate content were monitored in the milks of seven individual cows and six goats during lactation. Lactoperoxidase activity exhibited a cyclic pattern with alternating peaks and troughs throughout lactation. Extremely large variations were observed between and within animals. For example, lactoperoxidase activity ranged from 0n05-5n60 U\ml for one cow on different sampling days. Variations between cows were also large, ranging from 0n98-5n1 U\ml on a specific samplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
4
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 10 publications
7
53
4
2
Order By: Relevance
“…Lactoperoxidase concentration is linked to lactation period [32]. Thiocyanate concentrations in the milk samples fell within the range described in the literature (between 1 and 15 µg·mL -1 ; [7,15]). Thiocyanate concentration in milk depends on the animal's diet.…”
Section: Analysis Of the Eight Milk Samples Used To Evaluate Effect Omentioning
confidence: 78%
“…Lactoperoxidase concentration is linked to lactation period [32]. Thiocyanate concentrations in the milk samples fell within the range described in the literature (between 1 and 15 µg·mL -1 ; [7,15]). Thiocyanate concentration in milk depends on the animal's diet.…”
Section: Analysis Of the Eight Milk Samples Used To Evaluate Effect Omentioning
confidence: 78%
“…The activities fall either side of that of 6.55 U ml -1 reported by Back & Thomson (2005), although that study did not report the pasture intake of the cows. Fonteh et al (2002) reported large BC and WC variation in LP activities. The WC variation was at least 10-fold larger than BC.…”
Section: Discussionmentioning
confidence: 96%
“…Little information is available on factors that affect LP activity other than stage of lactation, breed and SCC (Reiter 1985;Fonteh et al 2002;Back & Thomson 2005). In this current study, all cows were at the same stage of lactation, the same breed and no difference was found in average SCC between the two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For neutralization measurements of purified HBC IgG, IgG concentrations were equalized to better reflect the IgG-mediated neutralizing activity. The presence and concentrations of antimicrobial components within BC, including lactoferrin, lysozyme, or lactoperoxidase, vary considerably among healthy cows, are highly dependent on the exact timing of BC collection, and could therefore significantly influence the neutralization profile of HBC (12,15,38,55). We mapped the Ab-binding sites within gp140 conferring the neutralizing activities in purified HBC IgG from both NP cows using competition with MAbs with defined epitopes.…”
Section: Discussionmentioning
confidence: 99%